Characterization of whole-body vibration for monorail passenger ride comfort - Jamali, Qadir Bakhsh (2018)
Train travel has always been a major mode of public transport in developed countries. In the inner cities monorails are often used, which are operated at elevated rail or beam, the main advantage being traffic interactions can be minimized while maintaining its original landscape. Ride comfort is the basic requirement for every passenger in all kind of public transports. In monorail, vibration is considered as major factor of discomfort, it transmitted to human body, which contribute many health issues. The aim of this study was to evaluate the whole-body vibration transmission and the effects to the monorail passengers. There were total of twenty-four experiments conducted in a two-car train monorail on its complete line from Kuala Lumpur Sentral to Titiwangsa stations. Human vibration meter (HVM-100) with tri-axial accelerometer pad was used to measure the WBV of passengers and International Standards Organization (ISO) 2631-1: 1997 was used for analysis. The experimental results show that the daily vibration exposure 0.81 m/s2 was higher than the action value 0.5 m/s2 of the standard during peak operation and 0.82 m/s2 during off-peak operation. The health effect was measured 9.90 m/s1.75 during peak operation and 9.94 m/s1.75 during off-peak operation; both values are observed in moderate health effect zone as per standard (8.5 m/s1.75 to 17 m/s1.75). Moreover, the passenger ride comfort was measured, it was found to be fairly-uncomfortable at rear bogie and not-uncomfortable at center of car. The statistical analysis has proven the significance of orientation, location and operating hours by significant value p = 0.000 (i.e. p < α) with 29.5% of the variance has been accounted between groups. This provides justification to standardization of proper priority seating zone. The findings of this study can assist in the standard specification for seating design of monorail. The statistical analysis shows that all results are statistically significant for orientations, locations as well as operations.